Developing a Wordwall-based Talk or Dare Card to Teach Speaking Skills: Tathwiir Bithaaqat Talk or Dare al-Mu'tamidat 'ala Wordwall li Ta'liim Mahaarat al-Kalaam - Viky Zakiyah Fuadah; Hasan Syaiful Rizal; Mochamad Hasyim (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to develop a speaking skills learning medium in the form of Talk or Dare cards based Wordwall for primary school students. This study is based on the need for innovative media that can increase student engagement in language learning. This study employs the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques involve observation, interviews, tests, questionnaires, and documentation. The results of the study indicate that the product's feasibility is rated at 81% by media experts and 86% by subject matter experts, meeting the criteria for ‘highly feasible.’ The effectiveness of the product was seen from the increase in the average N-gain of 0,6977, which falls into the moderate category, and the t-test result of 13,606 with a significance level (sig. 2-tailed) of 0.001. The novelty of this research lies in the integration of gamification concepts in Arabic language learning media through an attractive digital platform. This medium provides more interactive and contextual learning for primary school students. This study contributes to Arabic language pedagogy by integrating gamification and digital platforms to enhance speaking skill learning in primary schools. ملخص يهدف هذا البحث إلى تطوير بطاقة Talk or Dare المعتمدة على Wordwall لتكون وسيلة تعليمية لمهارة الكلام لدى التلاميذ في المدرسة الابتدائية. ويستند هذا البحث إلى الحاجة الماسّة إلى وسيلة مبتكرة تسهم في تعزيز مشاركة التلاميذ النشطة في تعلم مهارة الكلام. وقد استخدم في هذا البحث طريقة البحث والتطوير (R&D) باستخدام نموذج ADDIE الذي يشمل مراحل التحليل والتصميم والتطوير والتنفيذ والتقويم. نفذت طرق جمع البيانات عن طريق الملاحظة، المقابلة، الاختبار، الاستبانة، والتوثيق. وقد أظهرت نتائج البحث أن صلاحية المنتج من قبل خبير الوسائط بلغت ٨١٪، ومن قبل خبير المادة بلغت ٨٦٪، وهما ضمن معيار صالح جدا. أما فاعلية المنتج فقد تجلّت من خلال ارتفاع متوسط درجة N-gain هو ٠٫٦٩٧٧. فإنه يعد من الفئة المتوسطة. تحصيل اختبار t  ١٣٬٦٠٦ مستوى الدلالة sig-2 tailed   ٠٫٠٠١ . وتكمن جدة هذا البحث في دمج مفهوم التلعيب في وسيلة تعليم اللغة العربية، من خلال منصة رقمية جذابة. وتوفّر هذه الوسيلة تجربة تعليمية أكثر تفاعلا وسياقا للتلاميذ في المدرسة الابتدائية. ويسهم هذا البحث في تطوير تعليم اللغة العربية، من خلال دمج عناصر التلعيب والتقنية الرقمية لتعزيز تعليم مهارة الكلام في المدرسة الابتدائية.